Linking organizational justice with organization citizenship behaviors: Collectivism as moderator - Asif Shahzad; Muhammad Ayub Siddiqui; Muhammad Zakaria (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2014)
The study examines the link between organizational justice (OJ) and organizational citizenship behaviors (OCB) using collectivism (COLL) as moderating variable in Pakistan. Survey based data is collected using questionnaire from 350 respondents of six public sector universities in Pakistan. The Cohen model was used for testing the moderating effect of collectivism. Empirical results show significant positive link between organizational justice and OCB, and that collectivism moderates positively in organizational justice and OCB link. The results imply that the leader's success at workplace depends upon treating employees with justice. Additionally, Logit model was also used to test the moderating effect of collectivism in the relationship of OJ and OCB link. This study is an important contribution to the existing literature as it employs Cohen model and logit model together in the field of organizational behavior.
Keywords: 330; organizational justice; OCB; collectivism; moderation